Is it practically possible to comply with the qualifying interest requirement when entering into a section 42 asset-for-share transaction concerning immovable property, given the applicable time of disposal rules and the application of the Companies Act? - Stronkhorst, Angelique (Department of Finance and Tax, 2025)
The South African Income Tax Act No 58 of 1962 (“the ITA”) contains several group relief provisions aimed to facilitate corporate restructuring. In the ITA there are various examples of roll-over relief provisions generally that contain no time restrictions, nor which are determined with reference to a specific moment in time. That notwithstanding, section 42 of the ITA, colloquially known as referring to asset for-share transactions, requires a transferor company (the company disposing of an asset) to hold a qualifying interest in a transferee company (the company receiving the asset in exchange for the issue of shares) at the close of day on which the asset is disposed of. Accordingly, the ITA is prescriptive regarding the timing provision and when a qualifying interest in section 42 is required to be held. In this study, the author considers the practical application of the qualifying interest requirement and how compliance with this requirement is problematic when considering other legislative enactments. In doing so, the author identifies possible impediments for compliance with the section 42 qualifying interest requirement and furthermore attempts to adopt an interpretation in which the legislative enactments can either be reconciled or interpreted widely to ensure that the requirements of the ITA are complied with. The aim of this study and the question that the author attempted to address in its analysis above is whether it is practically possible to comply with the qualifying interest requirement when entering into a section 42 asset-for-share transaction concerning immovable property, given the applicable time of disposal rules and the application of the Companies Act? In this study and as part of the key findings of this paper, the author identifies several ambiguities arising from the application of various legislative enactments. The Companies Act and the impediments imposed by it to comply with the “qualifying interest” requirement enacted in section 42 of the ITA, specifically insofar as the issue of shares for adequate consideration is concerned in clearly highlighted by the author. To align the provisions of the various legislative enactments and in an attempt to reconcile them the author argued that a purposive approach to statutory interpretation should be adopted in which the practical application and functionality of the provision should be called into question.